2021
DOI: 10.1016/j.jaerosci.2021.105783
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of soot deposit on a resistive sensor: Proposal of an experimental calibration protocol

Abstract: During a fire in an industrial facility, the main consequences concerning aerosol are the production of large amount of soot and potential resuspension of hazardous material in particulate form. Soot deposition quantification on walls in a room during a fire is essential for the prediction of aerosol quantities that can be transported in the ventilation ducts and clog high efficiency particulate air filters. For this purpose, accumulative resistive sensors, initially developed for monitoring Diesel Particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Mensch & Cleary (2018) used resistive sensors for a first attempt to quantify soot deposits formed by thermophoresis within a temperature gradient imposed between thermally regulated rectangular flow chanel. According to this literature review, corresponding soot deposited mass per surface area are ranging from 20 to nearly 350 mg.m -2 , values confirming the relevance of the quantification method introduced by Kort et al (2021). Nevertheless, additional measurements, carried out during real-scale and confined fire experiments (Kort et al, 2019) have demonstrated that significantly higher mass deposit (up to 25 g.m -2 ) could be obtained under realistic conditions, limiting the range of application of the quantification method introduced by Kort et al (2021).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Mensch & Cleary (2018) used resistive sensors for a first attempt to quantify soot deposits formed by thermophoresis within a temperature gradient imposed between thermally regulated rectangular flow chanel. According to this literature review, corresponding soot deposited mass per surface area are ranging from 20 to nearly 350 mg.m -2 , values confirming the relevance of the quantification method introduced by Kort et al (2021). Nevertheless, additional measurements, carried out during real-scale and confined fire experiments (Kort et al, 2019) have demonstrated that significantly higher mass deposit (up to 25 g.m -2 ) could be obtained under realistic conditions, limiting the range of application of the quantification method introduced by Kort et al (2021).…”
Section: Introductionsupporting
confidence: 56%
“…According to this literature review, corresponding soot deposited mass per surface area are ranging from 20 to nearly 350 mg.m -2 , values confirming the relevance of the quantification method introduced by Kort et al (2021). Nevertheless, additional measurements, carried out during real-scale and confined fire experiments (Kort et al, 2019) have demonstrated that significantly higher mass deposit (up to 25 g.m -2 ) could be obtained under realistic conditions, limiting the range of application of the quantification method introduced by Kort et al (2021). Thus, the aim of this work is to develop an additional measurement devices able to quantify such high soot deposit contamination levels in a direct, non-invasive, representative and complementary way to the quantification method proposed by Kort et al, (2021).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…These sensors are sensitive to ambient conditions, such as relative humidity and the orientation of the sensors is also important (Kort et al 2019(Kort et al , 2021. with the mass loading.…”
Section: Soot Sensors (Conductive Particles) 36mentioning
confidence: 99%